THE APPLICATION OF ARTIFICIAL INTELLIGENCE TO INDONESIAN E-COMMERCE PLATFORMS AND ITS IMPACT ON DIGITAL ECONOMIC GROWTH - Annisa, Vanessa Nurul; Rafidah, Rafidah; Rahma, Sri; Rosmanidar, Elyanti; Pratiwi, Army Setia (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study explores the implementation of Artificial Intelligence (AI) in Indonesian e-commerce platforms and its impact on digital economic growth. The findings highlight three key aspects. First, AI has transformed e-commerce operations through personalized product recommendations, natural language processing (NLP) chatbots, and dynamic pricing systems, which enhance customer experience, increase sales, and build loyalty. Second, AI contributes significantly to business efficiency and growth by integrating with Business Intelligence to accelerate data analysis, support accurate decision-making, and reduce operational costs, while automation enables firms to optimize resources and develop new digital business models. Third, AI strengthens Indonesia’s digital economy by expanding market access, especially for micro, small, and medium enterprises (MSMEs), and by fostering digital financial inclusion through AI-driven services such as credit scoring and micro-lending. With projections estimating Indonesia’s digital economy to reach USD 130 billion by 2025, AI is recognized as a critical driver for inclusive and sustainable growth. Nevertheless, its success depends on supportive infrastructure, skilled human resources, and adaptive regulations to balance innovation with consumer protection.